Der Status von Flüchtlingen in zwei deutschsprachigen Romanen aus der Perspektive des raumtheoretischen Ansatzes von Bernhard Waldenfels - Leskovec, Andrea (Ars et humanitas, 2019)
Bernhard Waldenfels distinguishes between a space which someone arranges and that he or she belongs to, and a place where someone is. So the subject is in one place and at the same time moves in a space. In general, there is a balanced tension between the location and distribution in space. If this relationship becomes unbalanced, places without space and spaces without places arise. The latter designates a space in which there are no singular identifications, no individual or situational here and now, whereby the existence of an ego in the sense of an individual becomes questionable. Places without spaces, on the other hand, signify a reduction to a here and now, where space is lost as a factor of affiliation, which ultimately leads to an absence of an ego, since it is not possible to locate or classify it in a space of belonging. The essay is an attempt to operationalise this spatial-theoretical approach to the analysis of literary texts, which focus on refugees.
Keywords: Kröger, Merle; Obexer, Maxi; pripadnost; sodobna nemška književnost; status beguncev; teorija prostora